2001
DOI: 10.1017/s0033291701003956
|View full text |Cite
|
Sign up to set email alerts
|

Religion as a cross-cultural determinant of depression in elderly Europeans: results from the EURODEP collaboration

Abstract: Background. The protective effects of religion against late life depression may depend on the broader sociocultural environment. This paper examines whether the prevailing religious climate is related to cross-cultural differences of depression in elderly Europeans. Methods. Two approaches were employed, using data from the EURODEP collaboration. First, associations were studied between church-attendance, religious denomination and depression at the syndrome level for six EURODEP study centres (five countries,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
53
2
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(68 citation statements)
references
References 38 publications
(30 reference statements)
9
53
2
4
Order By: Relevance
“…Church attendance is one of the most widely used measures to evaluate the extent of religious involvement (Behere et al 2013). One European study showed that regular church attendance was negatively associated with the prevalence of depression (Braam et al 2001), which was confirmed by another study demonstrating that more frequent participation in public worship services was associated with a lower level of depression (Hayward et al 2012). Using attendance at religious meetings as an indicator of religious involvement or religiosity, no consistent results surfaced in this study.…”
Section: Depressive Symptoms and Frequency Of Attendance At Religiouscontrasting
confidence: 50%
See 4 more Smart Citations
“…Church attendance is one of the most widely used measures to evaluate the extent of religious involvement (Behere et al 2013). One European study showed that regular church attendance was negatively associated with the prevalence of depression (Braam et al 2001), which was confirmed by another study demonstrating that more frequent participation in public worship services was associated with a lower level of depression (Hayward et al 2012). Using attendance at religious meetings as an indicator of religious involvement or religiosity, no consistent results surfaced in this study.…”
Section: Depressive Symptoms and Frequency Of Attendance At Religiouscontrasting
confidence: 50%
“…Since religion signifies social/emotional support, cognitive schema, and/or spiritual beliefs (Al-Kandari 2011;Seomun 2010), religion can enhance the capacity of an individual to cope with a variety of stresses arising from adverse life events, such as illness, relationship dissolution, and the death of a close relative (Koenig 2009;McFarland 2010;Park et al 2012a). Thus, religious support can reduce levels of depression and increase life satisfaction (Braam et al 2001;Park et al 2012a). A review on the role of religion in mental health reported that two-thirds of 93 observational studies had discovered significantly lower rates or symptoms of depressive disorders among religious people (Koenig 2009).…”
Section: Religious Affiliations Depression and Mental Healthmentioning
confidence: 99%
See 3 more Smart Citations